2014
DOI: 10.1155/2014/584314
|View full text |Cite
|
Sign up to set email alerts
|

Abeta(1-42) Enhances Neuronal Excitability in the CA1 via NR2B Subunit-Containing NMDA Receptors

Abstract: Neuronal hyperexcitability is a phenomenon associated with early Alzheimer's disease. The underlying mechanism is considered to involve excessive activation of glutamate receptors; however, the exact molecular pathway remains to be determined. Extracellular recording from the CA1 of hippocampal slices is a long-standing standard for a range of studies both in basic research and in neuropharmacology. Evoked field potentials (fEPSPs) are regarded as the input, while spiking rate is regarded as the output of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…The soluble forms of Aβ 1–42 peptide are pathological species present in AD that are widely used to investigate their contribution to the pathogenesis and progression of the disease (Selkoe & Hardy, ). In vitro acute application of Aβ 1–42 causes hippocampal hyperexcitability (Tamagnini et al, ; Varga et al, ) and deficits in LTP (Eslami et al, ; Kimura et al, ; Lei, Xu, & Li, ). Similarly, different in vivo experiments show that the administration of Aβ 1–42 triggers behavioral deficits because of alterations in neural excitability and LTP process (Kalweit et al, ; Sanchez‐Rodriguez et al, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soluble forms of Aβ 1–42 peptide are pathological species present in AD that are widely used to investigate their contribution to the pathogenesis and progression of the disease (Selkoe & Hardy, ). In vitro acute application of Aβ 1–42 causes hippocampal hyperexcitability (Tamagnini et al, ; Varga et al, ) and deficits in LTP (Eslami et al, ; Kimura et al, ; Lei, Xu, & Li, ). Similarly, different in vivo experiments show that the administration of Aβ 1–42 triggers behavioral deficits because of alterations in neural excitability and LTP process (Kalweit et al, ; Sanchez‐Rodriguez et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…We also asked for the mechanism by which an increase in GirK conductance could compensate the excess of neuronal excitability caused by Aβ (Nava‐Mesa et al, ; Tamagnini et al, ; Varga et al, ) and therefore, restore hippocampal synaptic plasticity mechanisms. Present data showed that ML297 was also able to preserve mechanisms needed for LTP induction from the deleterious effects of Aβ 1–42 , most likely by recovering the balance between excitatory and inhibitory neurotransmission in CA3—CA1 synapse acting mainly at post‐synaptic level on pyramidal cells, as we also reported in vivo (Sanchez‐Rodriguez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Administrations of soluble oAβ to cultured neurons (Cuevas et al, 2011), brain slices (Minkeviciene et al,, 2009; Varga et al,2014; Ren et al, 2014) or living animals (Orbán et al,2011; Busche et al, 2012) all induced significant hyperexcitability in hippocampal neurons. These findings are consistent with several AD mouse models in which elevated levels of Aβ are associated with altered neuronal activity, spontaneous seizures, and epileptiform discharges (Palop et al,2007; Brown et al, 2011; Kerrigan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, at physiological concentrations (pMnM), experimental evidence suggests A␤ has a role in normal brain functions including neurogenesis, longterm potentiation, and neurotransmitter modulation [7][8][9]. A␤ 42 binds to the ␣7 nicotinic acetylcholine receptor (␣7nAChR) with picomolar affinity [10] and activation of this receptor is known to stimulate glutamate release [11].…”
Section: Introductionmentioning
confidence: 99%